Bibliometric analysis and visualization of transdermal drug delivery research in the last decade: global research trends and hotspots - Chen, Xinghan; Xiao, Haitao; Shi, Xiujun; Zhao, Qiao; Xu, Xuewen; Fan, Ping; Xiao, Dongqin (Frontiers in Pharmacology, 2023)
Background: Transdermal delivery has become a crucial field in pharmaceutical research. There has been a proliferation of innovative methods for transdermal drug delivery. In recent years, the number of publications regarding transdermal drug delivery has been rising rapidly. To investigate the current research trends and hotspots in transdermal drug delivery, a comprehensive bibliometric analysis was performed. Methods: An extensive literature review was conducted to gather information on transdermal drug delivery that had been published between 2003 and 2022. The articles were obtained from the Web of Science (WOS) and the National Center for Biotechnology Information (NCBI) databases. Subsequently, the collected data underwent analysis and visualization using a variety of software tools. This approach enables a deeper exploration of the hotspots and emerging trends within this particular research domain. Results: The results showed that the number of articles published on transdermal delivery has increased steadily over the years, with a total of 2,555 articles being analyzed. The most frequently cited articles were related to the optimization of drug delivery and the use of nanotechnology in transdermal drug delivery. The most active countries in the field of transdermal delivery research were the China, United States, and India. Furthermore, the hotspots over the past two decades were identified (e.g., drug therapy, drug delivery, and pharmaceutical preparations and drug design). The shift in research focus reflects an increasing emphasis on drug delivery and control release, rather than simply absorption and penetration, and suggests a growing interest in engineering approaches to transdermal drug delivery. Conclusion: This study provided a comprehensive overview of transdermal delivery research. The research indicated that transdermal delivery would be a rapidly evolving field with many opportunities for future research and development. Moreover, this bibliometric analysis will help researchers gain insights into transdermal drug delivery research's hotspots and trends accurately and quickly.